Thermoluminescence response of flat optical fiber subjected to 9 MeV electron irradiations - Hashim, S.; Omar, S.S.C.; Ibrahim, S.A.; Hassan, W.M.S.W.; Ung, N.M.; Mandiraji, G.A.; Bradley, D.A.; Alzimami, K. (2015)
We describe the efforts of finding a new thermoluminescent (TL) media using pure silica flat optical fiber (FF). The present study investigates the dose response, sensitivity, minimum detectable dose and glow curve of FF subjected to 9 MeV electron irradiations with various dose ranges from 0 Gy to 2.5 Gy. The above-mentioned TL properties of the FF are compared with commercially available TLD-100 rods. The TL measurements of the TL media exhibit a linear dose response over the delivered dose using a linear accelerator. We found that the sensitivity of TLD-100 is markedly 6 times greater than that of FF optical fiber. The minimum detectable dose was found to be 0.09 mGy for TLD-100 and 8.22 mGy for FF. Our work may contribute towards the development of a new dosimeter for personal monitoring purposes. (C) 2014 Elsevier Ltd. All rights reserved.